Internship Hotspot Monitoring - Niezam, Nur Maisarah (IRC, 2020)
In this paper, I propose an automated system named as Internship Hotspot Monitoring that utilizes Microsoft 365 applications and services to obtain its aim and objectives. Each semester, Universiti Teknologi Petronas manages approximately 500 students for internship program. However, students face problems when searching for the right companies due to past cases experienced by the company and previous UTP students. IHM provides a clear visualized and interactive data of hotspot companies that students and supervisors can refer to, in order to choose the right company of undertaking for their internship program. As a result, students can save a lot of time and effort by avoiding the wrong companies.